First-price sealed-bid auction with additional price negotiations: Theoretical analyses and results of experiments - Kuśmierczyk, Paweł (Publishing House of the Wrocław University of Economics, 2009)
Auctions, which play a significant role in Western countries’ economies, are also becoming more and more popular in CEE countries. They are a simple, efficient and transparent procedure of making market transactions. An auction is a very broad term which can mean any design in which goods are allocated to economic agents. In standard auctions in which few buyers compete for one unit (or many units) of a particular good an auction mechanism allocates the good(s) to the bidder(s) offering the highest price(s). In a procurement auction the whole procedure is reversed. Few sellers compete and one of them will provide a specified good (or specified goods) and the auction mechanism allocates the good(s) to the bidder(s) offering the lowest price(s). (fragment tekstu)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 59, s. 269-277